POMCUT (Portable Multi-Cooking Utensil) / Assoc. Prof. Dr Hassnah Wee … [et al.] - Wee, Hassnah; Abdul Aziz, Izzat Zharfan; Abu Bakar, Haikal; Jamilul-Lail, Muhammad ‘Imran Hakim; Mohd Shukri, Muhammad Haiqal (Faculty of Computer and Mathematical Sciences, 2022)
There are numerous alternatives that travellers, particularly adventurers, can bring with them to their destinations. This item is known as a 'POMCUT,' which stands for 'Portable Multi-Cooking Utensil.' The main goal of this product is to make it easier for adventurers to cook and eat their meals. POMCUT comes with a stackable small pot and pan that is built-in with a heat diffuser, as well as a set of cooking utensils and a cutting board. For easy cleaning and cooking, the pot and pan are made of non-stainless metal. This product is ideal for adventurers who want to cook their meals on the go. POMCUT can also be used for household equipment due to its small size, easy handling, and relatively inexpensive.